2022
DOI: 10.3390/w14030428
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for the Maintenance of Green Infrastructure in Six Chinese Pilot Sponge Cities

Abstract: Due to the increasingly devastating impact of pluvial flooding on human beings’ lives and properties in cities, the use of green infrastructure to manage stormwater onsite is becoming more popular worldwide. The maintenance of green infrastructure to ensure its function has become one of the most pressing tasks facing policy makers. However, there is limited research regarding the willingness to pay the stormwater fee as a form of maintenance funding. This study utilized contingent valuation data obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 53 publications
3
13
2
Order By: Relevance
“…Our study showed that the socioeconomic backgrounds of the respondents contributed to the heterogeneity in residents’ preferences and their WTP for ecological improvement schemes. This outcome is in line with the study by [ 70 ]. Our findings are similar to the results of the study by [ 71 ], which used a similar approach to evaluate the attitudes and WTP values of local residents for deep-sea ecosystem conservation in England.…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that the socioeconomic backgrounds of the respondents contributed to the heterogeneity in residents’ preferences and their WTP for ecological improvement schemes. This outcome is in line with the study by [ 70 ]. Our findings are similar to the results of the study by [ 71 ], which used a similar approach to evaluate the attitudes and WTP values of local residents for deep-sea ecosystem conservation in England.…”
Section: Discussionsupporting
confidence: 93%
“…This is confirmed by the answers collected regarding the willingness to participate financially in the maintenance of urban green areas, for which only half of the sample was in favour. In fact, 26.0% of the sample was not willing to pay for the Frontiers in Environmental Science frontiersin.org maintenance of their city's GIs, a result that is close to that shown in other researches (Derkzen et al, 2017;Exposito et al, 2021;Qiao and Randrup, 2022. The main reason lies in the fact that, according to these respondents, the local administration has to take care of urban GIs (or because they feel that municipal taxes are already high).…”
Section: Discussionsupporting
confidence: 70%
“…Urban green infrastructure must be regularly maintained to perform its functions after construction [30][31][32]. However, in many countries, construction and maintenance funding is insufficient, limiting wider implementation of urban green infrastructure [33].…”
Section: Introductionmentioning
confidence: 99%
“…Sponge city construction approaches include conserving a city's original ecosystems, recovering and restoring destroyed ecosystems, and employing urban green infrastructure [39,44,45]. In 2019, all 30 pilot sponge cities completed project construction in their demonstration zones, but continuous implementation of urban green infrastructure to manage stormwater has not manifested [31,46,47]. The Chinese central government has invested a large amount of money in the construction of sponge cities but has not provided financial support for their maintenance, which may lead to the failure of urban green infrastructure achieving their functions [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation